The influence of work shifts on burnout for millennial chefs in The Western Cape, South Africa - Ita Geyser; Nicola Wakelin-Theron; Nadia Esterhuyse (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The purpose of this research was to determine whether longer work shifts of more than eight hours, contributed towards millennial chefs’ burnout levels. For this study, a quantitative research approach was adopted. The study comprised of two groups of millennial chefs, aged 25 to 39, who worked long hours (more than eight hours) as well as millennial chefs who worked shorter hours (eight hours or less). The Copenhagen Burnout Inventory was the instrument that was used to measure the Burnout levels of the chef participants. The results indicated that the chefs who worked longer hours where more burnt-out than the chefs who worked shorter hours. Personal Burnout had a large effect on the Burnout levels of the two different groups. Therefore, shift length could be considered a predictor of Burnout. The working hours of chefs has a major impact on their Burnout levels. Managers and owners of restaurants and hotels should adapt their working hours to decrease the Burnout levels of the chefs in their employment. The findings from this study will assist chefs to renegotiate working hours with their respective employees.